Two-stage processed CuSbS2 thin films for photovoltaics: Effect of Cu/Sb ratio. Issue 12 (15th August 2018) - Chalapathi, U.; Poornaprakash, B.; Ahn, Chang-Hoi; Park, Si-Hyun
Abstract: In recent years, CuSbS2 has attracted significant research interest because of its direct optical band gap of 1.5 eV, high optical absorption coefficient, p-type electrical conductivity, and composition involving earth-abundant and non-toxic precursor elements. We prepared CuSbS2 thin films by annealing chemically grown Sb2 S3 and sputter deposited Cu (Sb2 S3 /Cu) stacks in a graphite box, and studied the effect of the Cu/Sb ratio on the growth and properties of these films by varying the thickness of Cu while keeping the thickness of Sb2 S3 constant. The Cu/Sb ratio significantly impacted the phase purity, grain growth, and morphology of the CuSbS2 films. The CuSbS2 films prepared with a Cu/Sb ratio of 0.78 showed some unreacted Sb2 S3 and nonuniform grain growth. Upon increasing the Cu/Sb ratio from 0.85 to 0.97, the Sb2 S3 phase was consumed completely, and phase-pure CuSbS2 with homogeneous grain formation was obtained. These films exhibited an orthorhombic crystal structure with the (410) preferred orientation. Further increase in the Cu/Sb ratio from 1.28 to 1.52 resulted in a change in the growth direction along the (200) plane and the formation of several micron-sized grains with a compact morphology and Cu3 SbS4 secondary phase. The direct optical band gap of the films decreased from 1.52 to 1.48 eV when Cu/Sb ratio was increased from 0.91 to 1.28. The films exhibited p-type electrical conductivity and their electrical resistivity decreased with increasing Cu/Sb ratio. From this investigation it was clear that deviation in the Cu/Sb ratio from the stoichiometric proportion leads to inhomogeneous grain growth of CuSbS2 films, which affect the performance of devices using these films.